AUDIT TATA KELOLA SEKOLAH BERBASIS RISIKO TERHADAP PENINGKATAN MUTU PENDIDIKAN DI SMPS NURUL YAQIN - Riyadi, Slamet; Kaniati Amalia; Erny Roesminingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze risk-based school governance in improving the quality of education at SMPS Nurul Yaqin, located in Nogosari Village, Rambipuji District, Jember Regency. The study employed a qualitative approach with a descriptive research design. Data collection techniques included interviews, observations, and documentation. The research subjects consisted of the principal and teachers. Data analysis was conducted using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The results showed that school governance at SMPS Nurul Yaqin has implemented several principles of good governance, including participation, transparency, communication, accountability, and supervision. Decision-making processes are carried out collaboratively through meetings involving teachers, educational staff, and the foundation management. In addition, the school has implemented learning supervision and routine evaluations as forms of internal control. The school also develops educational quality improvement programs through workshops, teacher training, digital learning, and the implementation of Project-Based Learning (PjBL). However, several risks affecting educational quality were still identified, including limited facilities and infrastructure, low competency of some teachers, variations in students’ abilities, and inadequate discipline among educational staff. This study concludes that risk-based school governance at SMPS Nurul Yaqin has been implemented fairly well in supporting educational quality improvement. Nevertheless, strengthening internal control systems, improving teacher competency, and enhancing staff discipline are still necessary to achieve sustainable educational quality improvement. The findings of this study are expected to serve as evaluation material for schools in strengthening governance systems and educational risk management.